Synthesis and biological activities of novel mitochondria-targeted artemisinin ester derivatives. (1st May 2021) - Xu, Cangcang; Xiao, Linfan; Zhang, Xia; Zhuang, Tao; Mu, Lingli; Yang, Xiaoping
Graphical abstract: Six novel artemisinin ester hybrids were synthesized, in vitro antitumor activity against five cancer cell lines and mitochondria-targeted mechanism were examined. Compound 2c displays a great potential of highly effective and low cytotoxic drugs for ovarian cancer with targeting cancer cell mitochondria. Highlights: Six novel artemisinin ester derivatives were synthesized and evaluated for cytotoxicity. Compound 2c displayed a great potential of anti-ovarian cancer activity with high efficiency and low toxicity. Compound 2c targeted mitochondria and induced ovarian cancer cell apoptosis. ROS and heme contributed to the cytotoxicity and cellular apoptosis of compound 2c . Abstract: A series of novel artemisinin ester derivatives were designed and synthesized for targeting mitochondria. Cytotoxicity against SMMC-7721, HepG2, OVCAR3, A549 and J82 cancer cell lines was evaluated. Compound 2c (IC50 = 3.0 μM) was the most potent anti-proliferative molecule against the OVCAR3 cells with low cytotoxicity in normal HUVEC cells. The mechanism of action of compound 2c was further investigated by analyzing cell apoptosis, mitochondrial membrane potential (Δψm) and intracellular ROS generation. The results indicated that compound 2c targeted mitochondria and induced cell apoptosis. ROS and heme attributed to the cytotoxicity and cell apoptosis of compound 2c . These promising findings indicated the compound 2c could serve as a great candidate against ovarian cancer for further investigation.